STRESS-STRAIN RELATION FOR CONCRETE IN NONUNIFORM TENSION - Michael Zak (International Journal for Computational Civil and Structural Engineering, 2019)
Discrepancy between reported in the literature tensile stress-strain relations for concrete is addressed. A conclusion is reached that in the post-peak (softening) range of deformation the stress-strain relation is not unique and depends on the gradient of stress. A simplified variant of such a relation, intended for analysis of concrete beams with regard to the effect of size (the depth of section), is proposed.